Subsequent open-cardiac surgery after transcatheter aortic valve implantation-indications and outcomes. (14th October 2021) - Berger, T; Siepe, M; Uzdenov, M; Dees, D; Pingpoh, C; Kondov, S; Beyersdorf, F; Fagu, A; Rylski, B; Czerny, M; Schroefel, H; Neumann, F.-J; et al.
Abstract: Background: Transcatheter aortic valve implantation (TAVI) has been historically done in high-risk patients or patients who are deemed unfit for open-heart surgery. Despite high procedural success rates subsequent open surgery remains an issue, immediately after TAVI implantation or during follow-up as bailout strategy. Purpose: Aim of this study was to report on indications and clinical outcomes of patients who underwent open-cardiac surgery following TAVI. Methods: Between 01/2011 and 12/2020 our centre performed 3131 TAVI procedures. Twenty-seven patients (including patients in whom TAVI was performed in other centres) underwent subsequent open-heart surgery via cardiopulmonary bypass after previous TAVI. Demographic, intraprocedural data and indications for surgery were evaluated. The VARC-2 criteria were applied to report on clinical outcomes. Results: Twenty-seven patients (aged 79 [IQR 76–84]; 59.3% male) were operated on for endocarditis (n=11; 40.7%), 3 patients for annular rupture, severe paravalvular leak and severe stenosis, respectively as well as 1 patient each for severe tricuspidal valve regurgitation, valve thrombosis, malpositioning, valve migration, ostial right coronary artery obstruction, left ventricular rupture and type A aortic dissection. The interval between the index TAVI procedure to open surgery was 3 months (IQR 0–26 months). Eight patients underwent emergency subsequent surgery on the same day immediately after TAVI. The surgical data including the procedures are shown in Figure 1. Four patients died intraoperatively due to uncontrolled bleeding. Immediate procedural and procedural mortality was 25.9% and 40.7%, respectively and all-cause mortality was 51.9% (11/12 died for cardiovascular reasons). Figure 2 shows the Kaplan-Meier estimator for survival. Intraoperative, immediate, procedural and all-cause mortality in patients operated on immediately after TAVI was 25.0%, 25.0%, 37.5%, and 50% respectively. No disabling stroke was observed while a non-disabling stroke occurred in 1 patient. New permanent pacemaker implantation was needed in 3 patients (11.1%). One patient required an additional, second operation to remove a left ventricular thrombus as bailout procedure. One patient suffered from a persisting endocarditis and was discharged on permanent antibiotic intake. Conclusions: Subsequent open-heart surgery after TAVI is rare, but may urgently become necessary due to TAVI related complications or progressing other cardiac pathologies. Despite a substantial early attrition rate clinical outcome is acceptable and a relevant number of patients can be discharged after surgery for immediate life-threatening TAVI complications. The option of subsequent surgical conversion remains an indispensable tool in the setting of a modern heart team-based approach. These results substantiate recommendations regarding both, having a cardiac surgical service on site and performing TAVI as an interdisciplinary team. FUNDunding Acknowledgement: Type of funding sources: None.